PENGARUH KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN DI OUTLET MIXUE KOTA BANDUNG - Kintan Puteri Kemala; Nuniek Dewi Pramanik (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
This study aims to determine the impact of human resource competencies on employee performance at Mixue outlets in Bandung City. This research employs a descriptive quantitative method. A sample of 33 individuals was obtained using the Slovin formula. Data collection was carried out using a Likert scale questionnaire distributed to employees at various Mixue outlets in Bandung City. The author utilized data analysis techniques including validity testing, reliability testing, normality testing, heteroscedasticity testing, simple linear regression, coefficient of determination, and t-tests. The collected data were then processed using SPSS 25. Based on the research results, the t-test yielded a significant value of 0.001 < 0.05, indicating that the related variable has an impact. Furthermore, the coefficient of determination test resulted in an R Square value of 61.2%. Thus, based on the analysis conducted, it can be concluded that employee performance is influenced by human resource competencies.